Penerapan Metode Scrum Pada Aplikasi Pelayanan Umum Inspektorat Daerah - Muhammad Leo Candra; R.M. Nasrul Halim (STMIK Budi Darma, 2023)
Inspektorat Daerah Kabupaten Musi Banyuasin (ITDA Muba) is one of the institutions in Musi Banyuasin Regency that provides public services as a form of service to the public, especially the people of Musi Banyuasin Regency, South Sumatra. There are various types of public services provided by the Inspektorat Daerah Kabupaten Musi Banyuasin, such as requests for clearance letters, requests for character certificates, requests for speakers, and the KPK clinic service. Based on the conducted research, the Public Service Application (APU) of the Inspektorat Daerah Kabupaten Musi Banyuasin (ITDA Muba) can be successfully developed using the PHP programming language with the Laravel framework. This indicates that the appropriate technology selection can support the development of a reliable and efficient application. The development of APU ITDA Muba using the Scrum method has brought benefits in increasing the involvement of the Inspektorat Daerah Kabupaten Musi Banyuasin as a client. Active involvement of the client is crucial in the process of application design and development to ensure that their needs and expectations are met. By hosting the application on the internet, APU ITDA Muba can be accessed by the public without time and location constraints. People can submit service requests anytime and anywhere, providing greater convenience and accessibility. Therefore, if the Public Service Application (APU) of the Inspektorat Daerah Kabupaten Musi Banyuasin (ITDA Muba) continues to be developed to improve its quality, improvements in functionality and security should be considered. Thus, the application can become better in terms of usability and provide a higher level of security. Further development efforts will contribute to more effective and efficient public services